Derivations on Pseudoquotients - Majeed, A.; Mikusiński, P. (Український математичний журнал, 2013)
A space of pseudoquotients denoted by B(X, S) is defined as equivalence classes of pairs (x, f); where x is an element of a nonempty set X, f is an element of S; a commutative semigroup of injective maps from X to X; and (x, f) ~ (y, g) for gx = fy: If X is a ring and elements of S are ring homomorphisms, then B(X, S) is a ring. We show that, under natural conditions, a derivation on X has a unique extension to a derivation on B(X, S): We also consider (α, β) -Jordan derivations, inner derivations, and generalized derivations. Введено означення простору псевдочасток B(X, S) як класів еквiвалентностi пар (x, f), де x — елемент непорожньої множини X, f — елемент комутативної напівгрупи S ін'єктивних відображень із X у X; та (x, f) ~ (y, g), якщо gx = fy. Якщо X — кільце та елементи S є гомоморфізмами кільця, то B(X, S) є кільцем. Показано, що за природних умов похідна на X має єдине розширення до похідної на B(X, S). Також розглянуто (α, β)-жорданові похідні, внутрішні похідні та узагальнені похідні.